The Relationship between Peer and Family Factors with The Tendency for Aggressive Behavior in Adolescents - Rosyadi, Khairunnisa; Sari, Nova Nurwinda; Agata, Annisa (Inspirasi Foundation, 2025)
Introduction: Adolescence is a critical developmental stage characterized by significant biological, cognitive, and socio-emotional changes. Both peer and family factors have been identified as influential in shaping adolescent aggression. Objective: This study aims to examine the relationship between peer and family factors and the tendency of aggressive behavior among adolescents at SMP Negeri 1 Pulau Panggung in 2024. Method: A quantitative correlational study with a cross-sectional design was conducted involving 265 students selected through simple random sampling. Data were collected using validated questionnaires and analyzed with univariate and bivariate statistical methods, including the Pearson chi-square test. Results: The findings revealed a significant relationship between peer factors and aggressive behavior tendencies, with students experiencing poor peer influences showing higher aggression levels. Similarly, family factors were significantly associated with aggressive tendencies, where adolescents from less supportive family environments exhibited increased aggression. Statistical analysis confirmed these associations with p-values below 0.05. Conclusion: Peer and family environments play crucial roles in influencing aggressive behavior among adolescents. Interventions targeting positive peer interactions and supportive family dynamics are essential to mitigate aggressive tendencies. Future research should consider larger sample sizes and focus on developing effective strategies to reduce adolescent aggression.